Photoreceptive reaction spectrum effect and phototactic activity intensity of locusts’ visual display characteristics stimulated by spectral light - Liu, Qihang; Jiang, Yueli; Miao, Jin; Gong, Zhongjun; Li, Tong; Duan, Yun; Wu, Yuqing (International Journal of Agricultural and Biological Engineering, 2021)
To reveal the nature of locusts’ visual reaction when stimulated by light, and to clarify the regulation characteristics of locusts’ phototactic visual physiology and obtain good spectral light features for locusts’ phototactic action, this study investigated locusts’ visual spectrum response by characterizing their photoreceptive reaction to LED light using an AvaSpec fiber-optic spectrometer system. Locusts’ phototactic response to spectral light was compared using this system. The results showed that locusts’ visual reaction characterization presents a photo-induced vision spectrum effect and that by offsetting the main wavelength of light and the spectral peak intensity, a time-varying bio-regulation effect emerges. In addition, locusts’ visual regulation ability to UV light is higher than that to violet light, whereas their reaction intensity is lower than to violet light, and the visual bio-regulatory force of locusts’ visual system absorbing orange light to react sensitively becomes gradually higher than when absorbing green light as time goes on. Moreover, corresponding to nominal illumination with the same radiant energy and a visual spectrum response stimulated by UV, violet, orange, and green light, it appears that the visual spectrum window is symmetrical around 382 nm, 400 nm, 602 nm, and 530 nm, respectively, with no significant difference between spectral amplitudes and having a time-varying incremental characteristic with amplitude peak width. This indicates that the stimulus intensity of UV, violet, orange, and green light exceeds locusts’ visual tolerance, causing them to generate regulation inactivation as a visual physiological reaction, whereas the visual window response effect stimulated by UV light presents an illumination timeliness effect. Simultaneously, time-varying characteristics of locusts’ bio-behavior intensity show that light intensity can make up for locusts’ visual sensitivity differences at various spectral wavelengths. Presented with differential response time, photosensitive behavior intensity, and induction effect induced by orange light, time is superior for orange light, the stimulation effect caused by violet light is the strongest, and the phototactic synergy effect caused by UV light is the best.Keywords: Locusta migratoria manilensis, photoreceptive spectrum effect, visual reaction intensity, photosensitive activity effect, spectral illuminationDOI: 10.25165/j.ijabe.20211402.4758Citation: Liu Q H, Jiang Y L, Miao J, Gong Z J, Li T, Duan Y, et al. Photoreceptive reaction spectrum effect and phototactic activity intensity of locusts’ visual display characteristics stimulated by spectral light. Int J Agric & Biol Eng, 2021; 14(2): 19–25.